Technical and economic optimums in pork meat cuts in two regions of Mexico. - Rebollar-Rebollar, Samuel; Gómez-Tenorio, Germán; Callejas-Juárez, Nicolás; Guzmán-Soria, Eugenio; Hernández-Martínez, Juvencio (Agronomía Mesoamericana, 2014)
The aim of this study was to determine the optimal selling weight per pig carcass (S. scrofa ssp), based on performance in primary, secondary and tertiary cuts. The field data was obtained from February to June 2012 and came from 10 butcheries selected by intention. These butcheries located in the state of Mexico, and more specifically in Valle de Bravo (5) and Tejupilco (5), and slaughtered 50 pigs (98,6 ± 7,2 kg PV, age 150 ± 5 d) each one, at the Municipal Abattoir in each municipality. The data were processed using three univariate nonlinear statistical models (for dressing cuts vs. primary, secondary and tertiary), adjusted to production functions with diminishing marginal returns. The results indicated that for the model of primal cuts, the technical optimum level (NOT) and the optimum economical level (NOE) were obtained with a carcass weight of 94,47 kg and 90,96 kg, respectively, with corresponding monetary gains of US$ 162,1 and US$ 173,0. For the model of minor cuts, the NOT and NOE were reached at 85,40 and 85,36 kg of carcass weight, and the corresponding monetary gains were US$ 236,7 and US$ 236,9. Based on the model of tertiary cuts the NOT and NOE were 82,38 and 82,26 kg, equivalent to a profit of US$ 217,6 and US$ 217,9. We conclude that the sale of carcasses at maximum weight did not necessarily lead to the most profit, and that the most profit was actually derived from the sale of minor cuts.